How to keep tropical aquarium fish - Stuart, Jonathan (Tiger Books International, 1996)
A wide-ranging, illustrated guide to creating and maintaining a healthly aquarium covers everything the beginning hobbyist needs to know about freshwater and marine home aquariums, from establishing a flourishing ecosystem to overcoming problems.